Confirmation of PDZD7 as a Nonsyndromic Hearing Loss Gene. Issue 4 (July 2016) - Vona, Barbara; Lechno, Stanislav; Hofrichter, Michaela A. H.; Hopf, Susanne; Läßig, Anne K.; Haaf, Thomas; Keilmann, Annerose; Zechner, Ulrich; Bartsch, Oliver
Abstract : Objective: PDZD7 was identified in 2009 in a family with apparent nonsyndromic sensorineural hearing loss. However, subsequent clinical reports have associated PDZD7 with digenic Usher syndrome, the most common cause of deaf-blindness, or as a modifier of retinal disease. No further reports have validated this gene for nonsyndromic hearing loss, intuitively calling correct genotype–phenotype association into question. This report describes a validating second case for biallelic mutations in PDZD7 causing nonsyndromic mild to severe sensorineural hearing loss. It also provides detailed audiometric and ophthalmologic data excluding Usher syndrome in both the present proband (proband 1) and the first proband described in 2009 (proband 2). Design: Proband 1 was sequenced using a custom-designed next generation sequencing panel consisting of 151 deafness genes. Bioinformatics analysis and filtering disclosed two PDZD7 sequence variants (c.1648C>T, p.Q550* and c.2107del, p.S703Vfs*20). Segregation testing followed in the family. For both probands, audiograms were collected and analyzed for progressive hearing loss and detailed ophthalmic evaluations were performed including electroretinography. Results: Proband 1 demonstrated a prelingual, nonsyndromic, sensorineural hearing loss that progressed in the higher frequencies between 4 and 9 years old. PDZD7 segregation analysis confirmed biallelic inheritance (compound heterozygosity). Mutation analysis determined the c.1648C>T mutation as novel and reported the c.2107del deletion as rs397516633 with a calculated minor allele frequency of 0.000018. Clinical evaluation spanning well over a decade in proband 2 disclosed bilateral, nonprogressive hearing loss. Both probands showed healthy retinas, excluding Usher syndrome-like changes in the eye. Conclusions: PDZD7 is confirmed as a bona fide autosomal recessive nonsyndromic hearing loss gene. In both probands, there was no evidence of impaired vision or ophthalmic pathology. As the current understanding of PDZD7 mutations bridge Mendelian and complex phenotypes, the authors recommend careful variant interpretation, since PDZD7 is one of many genes associated with both Usher syndrome and autosomal recessive nonsyndromic hearing loss. Additional reports are required for understanding the complete phenotypic spectrum of this gene, including the possibility of high-frequency progression, as well as noise-induced hearing loss susceptibility in adult carriers. This report rules out all forms of Usher syndrome with an onset before 12 and 15 years old in probands 1 and 2, respectively. However, due to the young ages of the probands, this report is uninformative regarding older patients. Abstract : Mutations in PDZD7 have been associated with both syndromic and non-syndromic hearing loss. The first proband with a homozygous disruption of PDZD7 was published in 2009, exclusively exhibiting autosomal recessive non-syndromic hearing loss. All subsequent cases reported since then have associated PDZD7 mutations with either digenic Usher syndrome or as a modifier of retinal phenotypes. Herein, two probands are described with biallelic PDZD7 mutations and non-syndromic sensorineural hearing loss. Both probands were evaluated for retinal degeneration and disclosed healthy retinas, supporting the correct assignment of non-syndromic hearing loss with PDZD7 mutations.Supplemental Digital Content is available in the text.